Implementasi Kebijakan Pengembangan Agrowisata Sawah Paloh Naga Di Desa Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang - Yuli Roulina Sitanggang; Asima Yanty Sylvania Siahaan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Agrotourism is a tourist attraction that is built with a theme or concept by combining agricultural activities and tourism activities. The research method used is descriptive method with a qualitative approach. The results of this study indicate that the implementation of the Paloh Naga Agrotourism Development Policy in Denai Lama Village, Pantai Labu District, Deli Serdang Regency, there are problems such as human resources who do not have professionalism in managing Agrotourism, limited financial resources and the Denai Lama village community has not all had a role and responsibility as a good host for visiting tourists to create a conducive environment and atmosphere